Alpha-Gal Syndrome in Children: Peculiarities of a “Tick-Borne” Allergic Disease - Saretta, Francesca; Giovannini, Mattia; Mori, Francesca; Arasi, Stefania; Liotti, Lucia; Pecoraro, Luca; Barni, Simona; Castagnoli, Riccardo; Mastrorilli, Carla; Caminiti, Lucia; Marseglia, Gian Luigi; Novembre, Elio (Frontiers in Pediatrics, 2021)
The alpha gal syndrome is an allergic syndrome which comprises two clinical pictures: an immediate hypersensitivity to drugs containing alpha gal and a delayed hypersensitivity to the ingestion of red mammalian meat. This allergic syndrome is still under recognized and patients are often mislabeled with diagnosis as spontaneous urticaria or idiopathic anaphylaxis. Although less frequently, children could also be affected, especially in tick endemic area. In most cases a positive anamnesis for tick bites in months before the onset of symptoms is recorded. The clinical manifestations could range form asymptomatic cases to severe anaphylaxis. The most frequently used diagnostic test is the determination of specific IgE for alpha gal. Oral provocation test is usually reserved to unclear cases or to verify tolerance after diet. No long-term follow-up studies have been published, especially in children, although an elimination diet could lead to a decrease of specific IgE for alpha gal and a possible reintroduction of some avoided foods.